Test-positive rate at CT colonography is increased by rectal bleeding and/or unexplained weight loss, unlike other common gastrointestinal symptoms. (2015) - Hock, D.; Materne, R.; Ouhadi, R.; Mancini, I.; Aouachria, S.A.; Nchimi, A.
Abstract: Purpose: We evaluated the rate of significant colonic and extra-colonic abnormalities at computed tomography colonography (CTC), according to symptoms and age. Materials and methods: We retrospectively evaluated 7361 consecutive average-risk subjects (3073 males, average age: 60.3 ± 13.9; range 18–96 years) for colorectal cancer (CRC) who underwent CTC. They were divided into three groups according to clinical symptoms: 1343 asymptomatic individuals (group A), 899 patients with at least one "alarm" symptom for CRC, including rectal bleeding and unexplained weight loss (group C), and 5119 subjects with other gastrointestinal symptoms (group B). Diagnostic and test-positive rates of CTC were established using optical colonoscopy (OC) and/or surgery as reference standard. In addition, clinically significant extra-colonic findings were noted. Results: 903 out of 7361 (12%, 95% confidence interval (CI) 0.11–0.13) subjects had at least one clinically significant colonic finding at CTC. CTC true positive fraction and false positive fraction were respectively 637/642 (99.2%, 95%CI 0.98–0.99) and 55/692 (7.95%, 95%CI 0.05–0.09). The pooled test-positive rate in group C (138/689, 20.0%, 95%CI 0.17–0.23) was significantly higher than in both groups A (79/1343, 5.9%, 95%CI 0.04–0.07) and B (420/5329, 7.5%, 95%CI 0.07–0.08) ( p  < 0.001). Aging and male gender were associated to a higher test positive rate. The rate of clinically significant extra-colonic findings was significantly higher in group C (44/689, 6.4%, 95%CI 0.04–0.08) versus groups A (26/1343, 1.9%, 95%CI 0.01–0.02) and B (64/5329, 1.2%, 95%CI 0.01–0.02) ( p  < 0.001). Conclusion: Both test-positive and significant extra-colonic finding rates at CTC are significantly increased in the presence of "alarm" gastrointestinal symptoms especially in older patients.